Eksistensi Komunitas Pengekspor Telur Ikan Terbang Desa Kalukuang Kecamatan Galesong Kabupaten Takalar - Agus, Muhammad; Rahmawati, Rahmawati; Fahreza W, Muhammad (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
Export activities are a key factor in determining the economic cycle in our country. As we know, Indonesia, as a country rich in natural resources and oil and gas, is always actively involved in international trade. Takalar Regency, including the coastal area of Galesong, is a producer and exporter of flying fish eggs, and the marketing of flying fish eggs has penetrated the international market. The export destinations are Japan, China, and Korea. Flying fish eggs are beneficial for medicinal purposes.. Flying fish eggs can be a prime export commodity and also provide a source of income for fishermen and exporting groups. This thesis employs a qualitative, empirical research approach and employs the grounded research method, a method that examines the empirical world in depth, using data as a source of theory. The rationale for this method is to inductively draw conclusions and use data as a source of theory, attempting to construct processes, events, and authenticity. The research problem is to identify and obtain data regarding the existence of exporting groups in relation to fishermen and the community. Data collection instruments include interviews, observation, and documentation. The research was analyzed using an interactive model through three procedures: data reduction, data presentation, and conclusion drawing. Research results regarding the existence of the Galesong Baru Village exporter group in Takalar Regency, as well as responses from fishermen and the community, indicate that the presence of this exporter group can increase fishermen's income and improve the community's standard of living.